TEKANAN FLASHING OPTIMAL PADA PEMBANGKIT LISTRIK TENAGA PANAS BUMI SISTEM DOUBLE-FLASH - Rafif Tri Adi Baihaqi; Hensen P. K. Sinulingga; Muhamad Ridwan Hamdani (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Geothermal resources in Indonesia are hydrothermal system dominated by water, with characteristic about 20% steam and 80% water. The type of power plant in Indonesia currently used to utilize the source of water dominance is a single-flash system. Brine results from this flashing system still have a high temperature so it can still be used as a new energy source, which uses a double-flash system. This research makes a model of geothermal power plant double-flash system to utilize brine results from flashing so that obtained bigger power. The purpose of this research is to know the optimal flashing pressure in a double-flash geothermal power plant. In this research, the variation of pressure change used was 4 bar, 5 bar, 6 bar, 7 bar, 8 bar, and 9 bar. Based on the research results, it can be seen that maximum turbine power can be generated when the pressure change (ÃŽâ€P) of flashing is at 7 bar which generate power 9,575 MW with efficiency 82,68%.Keywords: brine, flashing, single-flash, double-flash, pressure change